Medical translation: a mapping of Brazilian dissertations and thesis written between 2002 − 2018 - Ferreira, Fábio; Malta, Gleiton (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2023)
This is a bibliometric mapping of studies conducted on medical translation in Brazil. The primary objective is to map master’s, doctoral, and post-doctoral studies from 2002 to 2018, identifying the topics covered, the institutions, and the geographic regions in which they were carried out. The significance of the present study lies in the fact that it indicates regions and institutions, where research on medical translation is conducted, and reveals the regions in which this type of study is scarce. In both cases, the mapping can serve as a reference for researchers who are interested in this area of knowledge. In addition, the mapping can offer input for the implementation of public policies that encourage the development of studies in the area. Data were collected in three digital platforms, namely Domínio Público, Biblioteca Digital de Teses e Dissertações, and Catálogo de Teses e Dissertações da CAPES, by means of typing different keywords in Portuguese, in the search windows available. Of the 14 studies found, 28.6% were doctoral dissertations and 71.4% were master’s theses. All of the studies were conducted in the southeastern and southern regions of Brazil. Cardiology and general biomedicine were the most frequent topics followed by anesthesiology, orthopedics, cardiovascular surgery, arterial hypertension, physiology, geriatrics, gerontology, nutrition, and pharmacy.